PENGARUH PROFITABILITAS, LEVERAGE DAN FINANCIAL DISTRESS TERHADAP EARNING MANAGEMENT DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Sari, Sonia Puspita; Hanun, Nur Ravita; Hanif, Aisha; Rahayu, Duwi (Universitas Muhammadiyah Palembang, 2024)
The information on profit in financial reports often becomes the main concern of investors and prospective investors. This condition demands the company’s management to implement certain strategies in generating profits in line with investor expectations. Managers usually implement strategies by practicing earnings management to manipulate financial reports. This study aims to determine the extent of the influence of profitability, leverage, and financial distress on earnings management with managerial ownership as a moderating variable. This study uses a quantitative method. The population in this study is food and beverage companies listed on the Indonesia Stock Exchange in 2020-2022. The research results show that profitability, leverage, and financial distress influence earnings management practices. Apart from that, managerial ownership in food and beverage companies is able to moderate the influence of profitability on earnings management. However, managerial ownership is unable to moderate the influence of leverage and financial distress on earnings management.